Effectiveness of the Posrembatam.com Web-Based Information System in Increasing Adolescents' Participation in Youth Health Posts - Yola Abdila Br Sianipar; Eka Fitri Amir; Nuari Andolina (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Adolescent health problems are becoming increasingly complex, including high rates of smoking, anaemia, and early pregnancy, as well as low participation in health promotion and prevention activities such as Adolescent Health Posts (Posyandu Remaja). Limited access to information and a lack of engaging educational media contribute to this low participation. This study aimed to determine the effect of the web-based information system Posrembatam.com on adolescent participation in Adolescent Health Post activities. A quantitative approach using a one-group pretest–posttest design was employed. The sample consisted of 62 adolescents from SMPN 62 Batam who received an intervention involving access to the Posrembatam.com website. The website provides information on adolescent health, activity schedules, map-based locations of Adolescent Health Posts, and interactive features. Data were collected using online questionnaires and analysed using descriptive statistics and the Wilcoxon signed-rank test. The results showed that all respondents considered the information provided on the website easy to understand and useful. Following the intervention, participation in Adolescent Health Post activities increased, with 51.9% of respondents participating and 48.1% not participating. The Wilcoxon signed-rank test showed a statistically significant difference in participation frequency before and after the intervention (p = 0.000; p < 0.05). Therefore, Posrembatam.com may serve as an effective web-based information system to support and improve adolescent participation in Adolescent Health Post activities.